Better care for babies: the added value of a modified reverse syphilis testing algorithm for the treatment of congenital syphilis in a maternity Hospital in Central African Republic - Oluwakemi F. Ogundipe; Rafael Van den Bergh; Behounde Thierry; Kudakwashe C. Takarinda; Claude P. Muller; Collins Timire; Severine Caluwaerts; Pascale Chaillet; Isabel Zuniga (BMC Pediatrics, 2019)
Abstract Background In high syphilis prevalence settings, the syphilis testing and treatment strategy for mothers and newborns must be tailored to balance the risk of over treatment against the risk of missing infants at high-risk for congenital syphilis. Adding a non-treponemal test (Rapid Plasma Reagin - RPR) to a routine rapid treponemal test (SD Bioline Syphilis 3.0) for women giving birth can help distinguish between neonates at high and low-risk for congenital syphilis to tailor their treatment. Treatment for neonates born to RPR-reactive mothers (high-risk) is 10 days of intravenous penicillin, while one dose of intramuscular penicillin is sufficient for those born to RPR non-reactive mothers (low-risk). This strategy was adopted in March 2017 in a Médecins Sans Frontières supported hospital in Bangui, Central African Republic. This study examined the operational consequences of this algorithm on the treatment of newborns. Methods The study was a retrospective cohort study. Routine programmatic data were analysed. Descriptive statistical analysis was done. Total antibiotic days, hospitalization days and estimated costs were compared to scenarios without RPR testing and another where syphilis treatment was the sole reason for hospitalization. Results Of 202 babies born to SD Bioline positive mothers 89 (44%) and 111(55%) were RPR-reactive and non-reactive respectively (2 were unrecorded) of whom 80% and 88% of the neonates received appropriate antibiotic treatment respectively. Neonates born to RPR non-reactive mothers were 80% less likely to have sepsis [Relative risk (RR) = 0.20; 95% Confidence interval (CI) = 0.04–0.92] and 9% more likely to be discharged [RR = 1.09; 95% CI = 1.00–1.18] compared to those of RPR-reactive mothers. There was a 52%, and 49% reduction in antibiotic and hospitalization days respectively compared to a scenario with SD-Bioline testing only. Total hospitalization costs were also 52% lower compared to a scenario without RPR testing. Conclusions This testing strategy can help identify infants at high and low risk for congenital syphilis and treat them accordingly at substantial cost savings. It is especially appropriate for settings with high syphilis endemicity, limited resources and overcrowded maternities. The babies additionally benefit from lower risks of exposure to unnecessary antibiotics and nosocomial infections.